Предмет: Алгебра,
автор: mara9997
3x*(x-2)-1=x-0,5*(8+x^2)
Ответы
Автор ответа:
0
3х^2-6x=x-4-0.5x^2
3x^2+0.5x^2-6x-4=0
3.5x^2-6x-4=0
D=36+12.5=48.5
3x^2+0.5x^2-6x-4=0
3.5x^2-6x-4=0
D=36+12.5=48.5
Автор ответа:
0
3x*(x-2)-1=x-0,5*(8+x^2)
3x^2 - 6x - 1 = x - 4 - 0,5x^2
3,5x^2 -7x + 3 = 0
35x^2 - 70x + 30 = 0
7x^2 - 14x + 6 = 0
D1 = 49 - 42 = 7
x1 = (7+корень из 7)/7
х2 = (7 - корень из 7)/7
3x^2 - 6x - 1 = x - 4 - 0,5x^2
3,5x^2 -7x + 3 = 0
35x^2 - 70x + 30 = 0
7x^2 - 14x + 6 = 0
D1 = 49 - 42 = 7
x1 = (7+корень из 7)/7
х2 = (7 - корень из 7)/7
Похожие вопросы
Предмет: Другие предметы,
автор: moskovskij04
Предмет: Обществознание,
автор: aleksand3rbur
Предмет: Литература,
автор: tarastrushko40
Предмет: Химия,
автор: Аноним